Effect of Different Arbuscular Mycorrhizal Fungi on Growth and Physiology of Maize at Ambient and Low Temperature Regimes. (5th May 2014) - Chen, Xiaoying; Song, Fengbin; Liu, Fulai; Tian, Chunjie; Liu, Shengqun; Xu, Hongwen; Zhu, Xiancan
Abstract : The effect of four different arbuscular mycorrhizal fungi (AMF) on the growth and lipid peroxidation, soluble sugar, proline contents, and antioxidant enzymes activities of Zea mays L. was studied in pot culture subjected to two temperature regimes. Maize plants were grown in pots filled with a mixture of sandy and black soil for 5 weeks, and then half of the plants were exposed to low temperature for 1 week while the rest of the plants were grown under ambient temperature and severed as control. Different AMF resulted in different root colonization and low temperature significantly decreased AM colonization. Low temperature remarkably decreased plant height and total dry weight but increased root dry weight and root-shoot ratio. The AM plants had higher proline content compared with the non-AM plants. The maize plants inoculated with Glomus etunicatum and G. intraradices had higher malondialdehyde and soluble sugar contents under low temperature condition. The activities of catalase (CAT) and peroxidase of AM inoculated maize were higher than those of non-AM ones. Low temperature noticeably decreased the activities of CAT. The results suggest that low temperature adversely affects maize physiology and AM symbiosis can improve maize seedlings tolerance to low temperature stress.